1994
DOI: 10.1159/000292530
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Related Protein during Pregnancy and the Perinatal Period

Abstract: To evaluate whether parathyroid hormone-related protein (PTHrP) plays any role in calcium metabolism during pregnancy and the perinatal period, we measured parathyroid hormone (PTH), immunoreactive PTHrP and calcium in maternal serum of women during pregnancy and puerperium, and in maternal and cord serum at delivery. Serum PTH levels in pregnant women were lower than those in nonpregnant women (p < 0.01). However, serum PTHrP levels were similar in the two groups of women. Cord serum total and ionic calcium l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…This is in line with the study of Bowyer et al 41 Seki et al 42 found a significantly lower PTH level in cord blood compared with maternal blood at birth, and this was in accordance with the results of Allgrove et al 43 who found low PTH levels in cord blood. They supported the contention that PTH secretion is suppressed by hypercalcemia in late fetal life, and thus Seki et al 42 suggest that stimulation of the placental calcium pump by PTHrP may be operative in humans, leading to low cord blood PTH at birth. In addition, one has to be aware that in the fetus PTH and calcium levels is probably of minor importance to circulating levels of 1,25(OH)2D, as 1,25(OH)2D levels primarily depend on the maternal supply of 25OHD.…”
Section: Maternal and Infant Vitamin D Status S Vij Streym Et Alsupporting
confidence: 91%
“…This is in line with the study of Bowyer et al 41 Seki et al 42 found a significantly lower PTH level in cord blood compared with maternal blood at birth, and this was in accordance with the results of Allgrove et al 43 who found low PTH levels in cord blood. They supported the contention that PTH secretion is suppressed by hypercalcemia in late fetal life, and thus Seki et al 42 suggest that stimulation of the placental calcium pump by PTHrP may be operative in humans, leading to low cord blood PTH at birth. In addition, one has to be aware that in the fetus PTH and calcium levels is probably of minor importance to circulating levels of 1,25(OH)2D, as 1,25(OH)2D levels primarily depend on the maternal supply of 25OHD.…”
Section: Maternal and Infant Vitamin D Status S Vij Streym Et Alsupporting
confidence: 91%
“…6 It has been suggested that this may be driven by parathyroid hormone (PTH); 7 however, more recent studies have shown a signi¢cant decrease in PTH during pregnancy and have suggested the possible involvement of parathyroid hormone -related protein (PTHrP). 8,9 Bone histology suggests an increase in resorption at this time, 10 and this is supported by recent studies of biochemical markers of bone turnover. 11,12 Bone mineral density measurements using dual-energy X-ray absorptiometry are di¤cult to interpret, however, with decreases at the spine but variable changes in appendicular skeleton being reported.…”
Section: Introductionsupporting
confidence: 57%
“…In the present study, sodium levels fell a maximum of 6 mEq/L and potassium levels fell a maximum of 0.7 mEq/L by day 22. Chloride levels decreased 7 mEq/L and then returned to preconceptional levels on day 25. Serum calcium levels in pregnant women have been reported as continuously decreasing throughout gestation (35,53) and as progressively decreasing until some time during the third trimester (week 29) with minimal increases thereafter (48,60). Some of the decrease is a response to the fetus's requirement for calcium (60).…”
Section: Methodsmentioning
confidence: 99%